Diagnostic informative value of liquid-based cytology optimized with genetic methods for the differential diagnosis of precancerous and malignant diseases of the cervix - O. I. Kit; A. Yu. Maksimov; M. Yu. Timoshkova; E. A. Lukbanova; N. A. Petrusenko; D. S. Potemkin; E. V. Verenikina; A. N. Shevchenko; M. M. Kecheryukova (Исследования и практика в медицине)
Purpose of the study. Was to assess diagnostic informative value of liquid-based cytology optimized with genetic methods for the differential diagnosis of precancerous and malignant diseases of the cervix.Materials and methods. The study included 381 patients. Cervical pathologies were diagnosed with liquid-based cytology only and liquid-based cytology optimized with genetic methods of assessing the expression of miRNA‑20a, miRNA‑375, miRNA‑21 and –23b. Results of liquid-based cytology and genetic methods were verified by histological examination of the material. Statistical analysis was performed using descriptive statistics methods with the calculation of the mean and standard error of the mean. The mean values were compared with the help of the Mann-Whitney test.Results. Diagnostic results of liquid-based cytology were consistent with histological results in 107 (73.8 %) of 145 cervical cancer (CC) patients, in 52 (57.1 %) of 91 patients with high-grade squamous intraepithelial lesions (HSIL), and in 30 (65.2 %) of 46 patients with low-grade squamous intraepithelial lesions (LSIL). Optimization of liquid-based cytology by assessing the expression of miRNA‑21 and miRNA‑23b in the cervical epithelium improved the diagnostic sensitivity of the method from 73.8 % to 80 %, and its specificity from 94.1 % to 97.9 %. The diagnostic sensitivity and specificity of liquid-based cytology for differential diagnosis of CC and HSIL was 87 % and 78.8 %, respectively. Optimization of liquidbased cytology by assessing the expression of miRNA‑20a and miRNA‑375 in the cervical epithelium for the differential diagnosis of CC and HSIL improved the diagnostic sensitivity of the method from 87 % to 95.1 %, and its specificity from 78.8 % to 93.9 %.Conclusions. We revealed the most informative pairs of miRNAs in the cervical epithelium, as an analysis of their expression expanded the possibilities of liquid-based cytology both as a method for diagnosing CC and as a method for the differential diagnosis between CC and HSIL.